2012 Sixth International Conference on Complex, Intelligent, and Software Intensive Systems 2012
DOI: 10.1109/cisis.2012.207
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model for Managing Emotions and Affections in Emotional Learning Platforms and Learning Experience in Emotional Computing Context

Abstract: In this paper we propose a model to represent and manage affective / emotional feedback. This model represents a set of emotions which is assumed to play a major role for learning processes. The emotions are to be identified during the learning phase. To achieve these objectives, we have considered primarily: i) Methods and techniques to assess and identify affectivity/ emotivity in ITS (Intelligent Tutoring System), ii) Feedback management derived by the detection of user's affective states in ITS. Our object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Six basic, universally recognized emotions were defined in 1972 by Ekman, Friesen, and Ellsworth: anger, disgust, fear, joy, sadness, and surprise. This list has been expanded by other researchers (e.g., Calvo & D'Mello, 2010;Ekman & Davison, 1994;Iovane et al, 2012). Methods and techniques for detecting affectivity have been proposed on the basis of these definitions (Luneski et al, 2010).…”
Section: Detection Methods and Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…Six basic, universally recognized emotions were defined in 1972 by Ekman, Friesen, and Ellsworth: anger, disgust, fear, joy, sadness, and surprise. This list has been expanded by other researchers (e.g., Calvo & D'Mello, 2010;Ekman & Davison, 1994;Iovane et al, 2012). Methods and techniques for detecting affectivity have been proposed on the basis of these definitions (Luneski et al, 2010).…”
Section: Detection Methods and Techniquesmentioning
confidence: 99%
“…Many studies have been carried out to describe how specific body features may be used to recognize specific affective states (Kleinsmith & Bianchi-Berthouze, 2013;Tan, Schöning, Luyten, & Coninx, 2013). Some researchers have focused on assessing only a reduced set of basic emotions, in a manner similar to that used in the facial expression technique, in order to simplify the posture-based affect detection process (Calvo & D'Mello, 2010;Iovane et al, 2012;Luneski et al, 2010). Head movement as a postural response also has been used to estimate attentional mechanisms when monitoring users' cognitive engagement (Dirican & Göktürk, 2012).…”
Section: Detection Methods and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulated recall comprises introspective procedures through which participants' cognitive processes help learners engage in more effective learning by adopting a stimulus (normally a recorded video) to be delivered to the student at the time of learning (Iovane, Salerno, Giordano, Ingenito, & Mangione, ). Bloom () observed that SR could be useful for examining humans' covert cognitive behavior.…”
Section: Literature Reviewmentioning
confidence: 99%